(untitled) (Journal of Fiber Bioengineering and Informatics, 2008)
Two kinds of antibacterial cotton fiber (called as C_14 and C_t) were prepared by bonding a gemini-type quaternary ammonium compound with a hydroxyl group in their spacer chain [1,5-bis(tetradecyl dimethyl ammonium iodide)-3- pentanol (called as DAP_14)] and a mono-type quaternary ammonium compound [N-tetradecyldimethyl (3-trimethoxysilylpropyl) ammonium chloride (called as TMMP)], respectively, to the surface of cotton fiber using a coupling agent, tetraethoxysilane. Antibacterial characteristic of C_14 was investigated comparatively with C_t. The experimental results indicated that C14 has higher antimicrobial activity than Ct against a broad range of microorganism, and average net bactericidal ratio against 15 strains of gram-negative, gram-positive bacteria and yeasts is 98.0% at 30&#176C and pH 6.0, which are 25.2 and 17.2 percentage point higher than those of C_t at treated time of 30min and 60min, respectively. Antibacterial activity of C_14 was hardly influenced by environmental pH and temperature, and could not be removed from the surfaces of cotton fiber by repeated washing with water.